Daily 6: An Approach to Foster Oral Fluency of English as a Foreign Language in Adolescents - Roso Freddy Cadena-Aguilar; Javier Hernando Ortega-Cuellar; Albedro Cadena-Aguilar (Profile: Issues in Teachers' Professional Development)
This action research study aimed to examine the possible impact of the Daily 6 approach on the oral fluency in English of 13 adolescents. This approach (extension of the existing Daily 5™ framework) introduced a sixth step, “speak to someone”, to respond to the lack of oral fluency limiting participants’ overall speaking performance in English as a foreign language. Data were gathered through surveys, diagnostic and achievement tests, and recordings using VoiceThread™. The coding and a small sample hypothesis test for means analysis unveiled the significance of the Daily 6 approach to enhance oral fluency through technology. Results displayed gains in oral fluency (length of runs, silent pauses, length of pauses, filled pauses, and pace) and positive changes in attitudinal responses within a low-anxiety environment.